PERLINDUNGAN HUKUM TERKAIT PERBEDAAN LUAS FAKTUAL DALAM PENGUKURAN OLEH PETUGAS UKUR TERHADAP LUAS YANG TERCANTUM DI DALAM SERTIPIKAT HAK ATAS TANAH DI KANTOR PERTANAHAN KOTA SURAKARTA - SISWANTO, AGUS (Dinamika Hukum, 2019)
The purpose of this article is intended to describe the procedures for measuring land parcels carried out by Land Office Measuring Officers along with their constraints, describing the factors that lead to the emergence of certificates of land rights which contain wide differences between factual conditions and the area listed in the certificate and analyze the construction of legal protection for measuring officers if they encounter cases of wide differences in accordance with the provisions. Certificate is the final result of all series of Land Registration activities. Land certificate is the strongest proof of proof for ownership of land rights in accordance with Article 19 Paragraph (2) letter c of Law Number 5 Year 1960 (UUPA) concerning Basic Agrarian Principles Regulations. Land certificates provide legal certainty both legal certainty regarding juridical data (subjects of land rights) and physical data (objects of land rights). Forms of legal certainty in juridical data include; status and legal basis to know and ascertain the basis of what land is acquired as well as Identity of rights holders, while guaranteeing the certainty of physical data includes certainty of location, boundaries, area, physical description of land and burden on land. But the reality now, many of which are found in the data in the certificate are different from the factual data in the field, especially the physical data of the land which is generally caused by the influence of the year or period of certificates and changes in the position of land boundaries whether intentional or not intentional change. This research method uses an empirical juridical approach that is to find theories about the process of occurrence and analyze / examine the workings of law in society. this approach to analyze the efforts of the Surakarta City Land Office in providing legal protection guarantees related to broad factual differences in measurement by officers measuring the area listed in the Certificate. In accordance with the explanation of Article 32 Paragraph (2) of Government Regulation Number 24/1997 above, the State does not fully guarantee the truth of the data contained in the Certificate so that if there is an error or non-conformity, corrections or corrections can be made as necessary in accordance with the applicable rules. Basing on the regulation that the measuring officer still gets legal protection related to the wide difference when the measuring officer is determined to carry out his duties in accordance with the prescribed rules. Keywords: Certificate; Physical Data; Area; Cadaster Surveyor; Legal protection